Lithium slag leach solution refining by hydroxide precipitation - Klimko, Jakub; Takacova, Zita; Marcinov, Vladimir; Piroskova, Jana; Vindt, Tomas; Liptai, Pavol; Orac, Dusan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Lithium-ion batteries contain many of critically important metals and their effective recycling is key for the sustainable development of the EU. In the past, only metals such as Co, Ni, and Cu were recycled by pyrometallurgy, and Li and Al were concentrated in the slags and not further processed. Novel approach of a black mass pyrometallurgical treatment propose possibility of further hydrometallurgical recycling of slags. In this paper, refining of solution obtained by leaching of slag in sulfuric acid is studied. Leach solution most valuable element is Li, but in addition it also contains Al, Si, Co, Mn, Ni and Cu, which removal is essential before high purity Li recovery is possible. Refining is performed by pH adjustment by addition of NaOH, which confirm the possibility of 100% removal of Al, Mn, 93.56% removal of Si, 86.36% removal of Cu and 61.75% removal of Co. Results also confirmed that solution refining by the addition of NaOH is causing lithium losses from 10% at pH 7 to 28% at pH 12, therefore it is proposed to combine more solution refining methods before pure Li2CO3 with minimum losses is precipitated.